PENGGUNAAN SHUUJOSHI YO DAN STRATEGI KESOPANAN DALAM FACE THREATENING ACT (FTA) - Damayanti, Maya; Aibonotika, Arza; Nimashita, Hana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study explains about the relationship of usage of final-sentence particle or shuujoshi yo on the imperative and negative imperative sentence in Japanese language and politeness strategy. The purpose of the research is to describe the use of sentence final-particle yo as a politeness strategy in Face Threatening Act (FTA). The data are imperative and negative imperative sentences that was collected from several dialogue in Japanese drama entitled Wakamonotachi. Theory of function and the use of sentence final-particle yo from Masuoka (1991) and Face Threatening Act (FTA)‟s theory and politeness strategy from Brown & Levinson (1987) are applied to analysis with qualitative descriptive approach. It has been found that sentence final-particle yo can be used on imperative and negative imperative sentence to avoid Face Threatening Act (FTA). The final-sentence can also be used to express the speaker‟s attitude to the listener that described politeness strategy.Key Words: Shuujoshi, final-sentence particle, imperative, Face Threatening Act (FTA), politeness strategy